Development and Control of a Quadruped Robot via SolidWorks and MATLAB/Simulink Modeling - Seabra, Bernardo Coimbra; Pizziolo, Tarcísio de Assunção; Brandão, Alexandre S. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
This paper describes the development, modeling and simulation of a quadruped robot, with an emphasis on generating stable walking patterns through kinematic control and dynamic analysis. The robot's three-dimensional structure was designed in a CAD environment, considering symmetry and mechanical feasibility criteria, and then imported into MATLAB/Simulink using the Simscape Multibody tool. The analytical equations were implemented in functional blocks in Simulink, allowing the joints to be actuated according to predefined trajectories. To ensure smooth and continuous movements, these trajectories were parameterized by third-degree Bezier curves. Gaits were defined as coordinated sequences, with independent phase, length and step height adjustments. Stability was assessed visually in Mechanics Explorer and quantified in MATLAB, which calculates in real time the support polygon formed by the legs in contact with the ground. The simulated results demonstrate the effectiveness of the gaits, keeping the center of mass within the stability zone.